2018
DOI: 10.1080/15700763.2018.1475574
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Educational Leadership During A Data-Based Decision Making Intervention

Abstract: School leaders are assumed to be important for the implementation of data-based decision making (DBDM), but little is known about changes in leadership during this implementation. Educational leadership was measured before, during, and after a two-year, school-wide DBDM intervention in 96 primary schools. Advanced analysis techniques were applied: educational leadership was classified based on multilevel latent class analysis, changes were modeled using multi-state modeling. Results indicate that leadership wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In fact, context is always a crucial factor in situations where leadership practices take effect (Bush, 2018). Using Teaching and Learning International Survey (TALIS) 2013 data, Liu (2020a) found that only Confucian Asia, with its high institutional collectivism, in-group collectivism and power distance, did not appear to have either a positive or a negative relationship with distributed leadership in seven country clusters, and that large-scale schools tended to have a distributed leadership pattern of decreased principal leadership but increased management team leadership (Liu, 2020b; Van Geel et al, 2018). Clearly, societal values influence the way principals perceive and enact their roles (Walker et al, 2012), but Chinese educational reforms have been decentralising power to local schools since the 1990s, and top- and mid-level teachers there participate in their schools’ pedagogical and administrative work under the principal accountability system to reach school-based management (Tian and Virtanen, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, context is always a crucial factor in situations where leadership practices take effect (Bush, 2018). Using Teaching and Learning International Survey (TALIS) 2013 data, Liu (2020a) found that only Confucian Asia, with its high institutional collectivism, in-group collectivism and power distance, did not appear to have either a positive or a negative relationship with distributed leadership in seven country clusters, and that large-scale schools tended to have a distributed leadership pattern of decreased principal leadership but increased management team leadership (Liu, 2020b; Van Geel et al, 2018). Clearly, societal values influence the way principals perceive and enact their roles (Walker et al, 2012), but Chinese educational reforms have been decentralising power to local schools since the 1990s, and top- and mid-level teachers there participate in their schools’ pedagogical and administrative work under the principal accountability system to reach school-based management (Tian and Virtanen, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Realizing change requires coordination and leadership and is more successfully achieved when school leaders involve teachers in leadership activities to ensure their commitment to educational change (e.g. Brown et al, 2017;DeMatthews, 2014;Klar et al, 2016;Van Geel et al, 2019). Previous studies (Aldaihani, 2019;Buske, 2018;DeMatthews, 2014;F.P.…”
Section: Introductionmentioning
confidence: 99%